2002
DOI: 10.1159/000057272
|View full text |Cite
|
Sign up to set email alerts
|

An Example on the Value of Non-Randomisation in Clinical Trials in Complementary Medicine

Abstract: Background : Randomised clinical trials may in principle show a small external validity. Non-randomised clinical trials therefore are sometimes regarded as an appropriate alternative when complementary and conventional treatments are compared. Objectives : To assess the value of advanced statistical methods in the process of estimating differences between a complementary and a conventional treatment of acute sinusitis in a non-randomised clinical trial. Methods : Multicentre, non-randomised, controlled clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…After further review of articles, 15 articles were excluded from further analysis as the outcomes were continuous and it was not possible to calculate an odds ratio or risk ratio [59,86,88,111,120,124,137,150,152,160,162,193,195,196,206]. For all selected reports published through 2003, we abstracted the following items: (i) the number of variables used to predict treatment and outcome, respectively; (ii) the unadjusted (crude) estimate for the treatment-outcome association; (iii) the estimates for the treatment-outcome association adjusted by use of PS matching, PS adjustment, and/or multivariable outcome models, including models without PS and with PS as well as covariates; (iv) the predictive value of the PS as assessed by the area under the receiver operating characteristic (ROC) curve (equivalent to the c-statistic in logistic regression); and (v) the percent of exposed participants that could be matched to unexposed participants (where applicable).…”
Section: Resultsmentioning
confidence: 99%
“…After further review of articles, 15 articles were excluded from further analysis as the outcomes were continuous and it was not possible to calculate an odds ratio or risk ratio [59,86,88,111,120,124,137,150,152,160,162,193,195,196,206]. For all selected reports published through 2003, we abstracted the following items: (i) the number of variables used to predict treatment and outcome, respectively; (ii) the unadjusted (crude) estimate for the treatment-outcome association; (iii) the estimates for the treatment-outcome association adjusted by use of PS matching, PS adjustment, and/or multivariable outcome models, including models without PS and with PS as well as covariates; (iv) the predictive value of the PS as assessed by the area under the receiver operating characteristic (ROC) curve (equivalent to the c-statistic in logistic regression); and (v) the percent of exposed participants that could be matched to unexposed participants (where applicable).…”
Section: Resultsmentioning
confidence: 99%
“…The application of variance analysis models using covariates, either by direct inclusion of multiple moderator variables or by taking the diversion to calculate a propensity score, improves the power of the results in a comparative study. In our case the two statistical techniques led to similar results, making the question of which method is more suitable a secondary one [13]. Instead, we consider the question concerning the nature of the relevant adjustment factors to be more important.…”
Section: Discussionmentioning
confidence: 59%
“…Unfortunately, this raises other problems which can invalidate the trial results. A detailed discussion on this topic is found in [22]. Generally, besides randomisation, our study showed two major problems.…”
Section: Discussionmentioning
confidence: 89%
“…In randomised trials which compare complementary and conventional therapies a small external validity can be expected [22]. We therefore recommend to perform a clinical trial which both a randomised and a non-randomised comparison.…”
Section: Discussionmentioning
confidence: 99%